An overview of the ambulance safety: Towards the improvement in ASEAN countries - Roslin, E. N.; Zakaria, M. Z.; Mohd Nur, N.; Ezrin Hani, Sukadarin; Widia, Mirta; Hamzah, A. (Society of Automotive Engineers Malaysia, 2021)
Ambulances have been utilized as one of the important vehiclesin operating the Emergency Medical Services (EMS) system.As safety is the utmost priority for an EMS crashes involving ambulances would not only delay patient transfers but would also endanger its occupants andother road users.Although the numbers ofaccidents involving ambulances are considered to be low as compared to other types of vehicles, preventive measures need to be taken in order to eliminate the high risk of accidents occurring as ambulances should be able to provide reliable and safe emergency transport services for the benefit of the public. An overview of ambulance accidents is highlighted in this paper. Based on the literature reviews, fourmain factors have been identified as the contributor to the causes of the accidents involving ambulances –driver-related factor, vehicle-related factor, task-related factor,and environment-related factor. From the findings, future research should be focused oncreating mitigation planson a structured preventive measure that could be implemented particularly in reducing fatal accidents involving the ambulance in ASEAN countries